STRATEGI PEMASARAN TANAMAN HIAS PADA MASA PANDEMI COVID-19 PADA TOKO BUNGA MBAK MEI DI KECAMATAN WLINGI KABUPATEN BLITAR - Apriyani, Nikolas; Kurniastuti, Tri; Wahyu Budiman, Eko (Universitas Islam Balitar, 2022)
This research was conducted to determine the factors contained in the internal and external environment of marketing and determine the right marketing strategy for ornamental plant companies during the Covid-19 pandemic at the Mbak Mei Flower Shop. The sampling method is a purposive sampling method and a SWOT matrix. Data collection using questionnaires and samples. The data analysis used is SWOT analysis and SWOT matrix. The results showed that the strength of this business is the quality of good customer service, having a large store, varied plants, affordable product prices, good crop quality. The downside is the lack of product promotion, the stock of plants brings in from other traders. The opportunity in this business is an increase in sales because the demand is increasing, according to current trends, receiving delivery services. The right marketing uses the S.O strategy by always maintaining the quality of service and plants, providing ornamental plants that are more popular with consumers and improving delivery services.